Hybrid Metaheuristic for Virtual Machine Scheduling in Cloud Computing - Sharma, Ritu; Mann, Palvinder Singh (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing is expanding as the next generation platform which would ease the user on pay as you use mode as per requirement. Cloud incorporates a set of virtual machine which comprises equally storage and computational facility. Due to speedy increase in use of Cloud Computing, moving of more and more application on cloud and demand of customers for more services and enhanced results. The fundamental goal of cloud computing is to offer successful access to isolated and geographically circulated resources. Cloud is growing every day and experience many problems such as scheduling. Scheduling means a group of policies to regulate the order of task to be executed by a computer system.VM Scheduling is necessary for efficient operations in distributed environment. This paper combines ant colony optimization and BAT to solve the VM scheduling problem. We discuss and evaluate these techniques in regard of various performance matrices to give an overview of the latest approaches in the field